(untitled) (International Journal of Food and Nutritional Sciences, 2021)
In this study, we synthesized thirteen derivatives by performing Steglich esterification on one or both phenolic rings of curcumin, aiming to enhance their anti-inflammatory activity. The monofunctionalized compounds exhibited superior bioactivity compared to the difunctionalized ones, particularly in terms of inhibiting IL-6 production. Among all the derivatives, compound 2 showed the highest activity in this regard. Additionally, compound 2 demonstrated strong activity against PGE2 synthesis. Through structure-activity relationship studies, we found that the presence of a free hydroxyl group or aromatic ligands on the curcumin ring, along with the absence of a linker moiety, contributed to increased activity. Compound 2 remained the most effective in modulating IL-6 production and showed potent activity against PGE2 synthesis.